ఆంధ్ర సారస్వత పరిషత్తు చరిత్ర ( 1943 - 1992 ) - (:unkn) unknown (Andhra Saraswata Parishath, 1992)
It tells us about the history of Andhra Saraswata Parishath
Andhra Saraswata Parishathu Charitra (1943 - 1992)
Keywords: Telugu; Literature; Telugu; Telugu